A Unique Method for Detecting and Characterizing Low Probability of Intercept Frequency Hopping Radar Signals by means of the Wigner-Ville Distribution and the Reassigned Smoothed Pseudo Wigner-Ville Distribution (Global Journals of Research in Engineering, 2022)
Low probability of intercept radar signals which are may times difficult to detect and characterize have as their goal to see but not be seen Digital intercept receivers are currently moving away from Fourier-based techniques and toward classical time-frequency techniques for analyzing low probability of intercept radar signals This paper brings forth the unique approach of both detecting and characterizing low probability of intercept frequency hopping radar signals by employing and comparing the Wigner-Ville Distribution and the Reassigned Smoothed Pseudo Wigner-Ville Distribution Four-component frequency hopping low probability of intercept radar signals were analyzed The following metrics were used for evaluation percent error of carrier frequency modulation bandwidth modulation period and time-frequency localization Also used were percent detection lowest signal-to-noise ratio for signal detection and relative processing time Experimental results demonstrate that overall the Reassigned Smoothed Pseudo Wigner-Ville Distribution produced more accurate characterization metrics than the Wigner-Ville Distribution An improvement in performance could potentially translate into saved equipment and lives